Glucose inhibition of glucagon secretion from rat alpha-cells is mediated by GABA released from neighboring beta-cells. - Wendt, A; Birnir, B; Buschard, K; Gromada, J; Salehi, A; Sewing, S; Rorsman, P; Braun, M (2004)
gamma-Aminobutyric acid (GABA) has been proposed to function as a paracrine signaling molecule in islets of Langerhans. We have shown that rat beta-cells release GABA by Ca(2+)-dependent exocytosis of synaptic-like microvesicles. Here we demonstrate that GABA thus released can diffuse over sufficient distances within the islet interstitium to activate GABA(A) receptors in neighboring cells. Confocal immunocytochemistry revealed the presence of GABA(A) receptors in glucagon-secreting alpha-cells but not in beta- and delta-cells. RT-PCR analysis detected transcripts of alpha(1) and alpha(4) as well as beta(1-3) GABA(A) receptor subunits in purified alpha-cells but not in beta-cells. In whole-cell voltage-clamp recordings, exogenous application of GABA activated Cl(-) currents in alpha-cells. The GABA(A) receptor antagonist SR95531 was used to investigate the effects of endogenous GABA (released from beta-cells) on pancreatic islet hormone secretion. The antagonist increased glucagon secretion at 1 mmol/l glucose twofold and completely abolished the inhibitory action of 20 mmol/l glucose on glucagon release. Basal and glucose-stimulated secretion of insulin and somatostatin were unaffected by SR95531. The L-type Ca(2+) channel blocker isradipine evoked a paradoxical stimulation of glucagon secretion. This effect was not observed in the presence of SR95531, and we therefore conclude that isradipine stimulates glucagon secretion by inhibition of GABA release.